PENGRAJIN TAHU DAN TEMPE DI LINGKUNGAN VII KELURAHAN BAHU KECAMATAN MALALAYANG KOTA MANADO - Prasetyo, Budi (Universitas Sam Ratulangi, 2016)
Craftsmen is one of the very noble profession that is trying to preserve one of the cultural heritage of our ancestors in any form including culinary , lack of attention on the craftsmen making craftsmen in Indonesia as a profession less attractive to a handful of people who prefer to work in large companies. Tofu and tempeh in the shoulder village is a cottage industry with workers kumlah less than 10 people who have to work up to 12 hours , long amounts of time is caused due to lack of manpower and demand from consumers . The work that already exist in Indonesia , especially in the shoulder in the environment VII must in order to keep and preserve our children and grandchildren can enjoy the result of the culture that has been there and not extinct by other foods from the outside. Â Â Keyword: Â Craftsmen, Cuture, Economy System, And Adaptation Strategy